A Case Series of 35 Hip Revisions for Adverse Reactions to Metal Debris following Cormet Hip Resurfacing. Issue 6 (November 2014) - Norris, Rory J.; McArthur, John; Parsons, Helen; Smith, Nicholas A.; Sprowson, Andrew P.; Foguet, Pedro
The primary aim of this study was to analyse our painful metal-on-metal (MoM) hip resurfacing revisions with evidence of 'adverse reactions to metal debris' (ARMD). In our series of 35 revisions the median whole blood Cobalt levels were 58 nmols/l (range 12-1407 nmols/l), and whole blood Chromium levels were 73 nmols/l (range 2-353 nmols/l). Thirty-four of our 35 patients had abnormal imaging on Ultrasound scanning (USS). The mean histological Campbell grading of ARMD was 4, and ranged from 0-9. The mean Oxford Hip Score (OHS) increased from 19 pre-revision (range 4-46) to 33 post-revision surgery (range 23-47). We found no correlation between the preoperative metal ion levels, and the severity of the disease or the outcome. Pain following hip resurfacing may arise from a number of causes and when groin pain arises in conjunction with abnormal cross sectional imaging we have offered our patients revision surgery regardless of raised metal ions or grossly abnormal imaging, with good results.